2013
DOI: 10.1590/s0100-736x2013001200004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of virulence-associated genes in Salmonella Enteritidis isolates from chicken in South of Brazil

Abstract: RESUMO.-[Detecção de genes associados à virulência em cepas de Salmonella Enteritidis isoladas de frangos na região sul do Brasil.] Salmonella spp. estão entre os principais agentes causadores de doenças transmitidas por alimentos, e o sorovar Salmonella Enteritidis é o mais frequentemente isolado no mundo. A virulência de Salmonella spp. e a sua interação com o hospedeiro são processos complexos que envolvem fatores de virulência para sobreviver às defesas do hospedeiro. O objetivo deste estudo foi detectar g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
47
3
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 37 publications
30
47
3
14
Order By: Relevance
“…Table 7 revealed that all isolates from diarrheic and slaughtered ducks harbor invA gene and amplified at 284bp fragments. These results were agreed with Borges et al [21] S. Typhimurium isolated from diarrheic ducks had pef gene and had 60%pathogenicity in mice , but S. Typhimurium isolated from slaughtered ducks had no genes and lower in pathogenicity in mice 40%. Also S. Virchow isolated from diarrheic ducks contain no pef gene although it differ in pathogenicity 40% in adults and 60% in small ducks and also S. Kentucky from diarrheic ducks one contain pef gene and other had no gene although pathogenicity in both 60% , S. Infants had no stn gene and not enterotoxigenic , S. Virchow had stn gene and not enterotoxigenic (this indicated that may gene not expressed).…”
Section: Resultssupporting
confidence: 92%
“…Table 7 revealed that all isolates from diarrheic and slaughtered ducks harbor invA gene and amplified at 284bp fragments. These results were agreed with Borges et al [21] S. Typhimurium isolated from diarrheic ducks had pef gene and had 60%pathogenicity in mice , but S. Typhimurium isolated from slaughtered ducks had no genes and lower in pathogenicity in mice 40%. Also S. Virchow isolated from diarrheic ducks contain no pef gene although it differ in pathogenicity 40% in adults and 60% in small ducks and also S. Kentucky from diarrheic ducks one contain pef gene and other had no gene although pathogenicity in both 60% , S. Infants had no stn gene and not enterotoxigenic , S. Virchow had stn gene and not enterotoxigenic (this indicated that may gene not expressed).…”
Section: Resultssupporting
confidence: 92%
“…spvC gene (located on virulence plasmid) product promotes rapid growth and survival of Salmonella spp. within host cells (Borges et al 2013). Results showed that the prevalence of invasion (sefA and invA) and TTSS associated genes (hila, avrA and sopE) are high in internalized Salmonella isolates which indicates probable mechanisms of internalization of the isolates.…”
Section: Discussionmentioning
confidence: 94%
“…In the evaluation of biofilm production, it was used the polyethylene microplates and capsule production technique according to Stepanovic et al (2004) and Rodrigues et al (2006), respectively. The virulence factors of salmonella were researched, represented by the genes IpfA, agfA, sefA, invA, hilA, avrA, sopE, sivH,e spvC, using the Polymerase Chain Reaction (PCR) method described by Borges et al (2013). The lineages were submitted to the carbapenems antibiotic resistence test by the disk diffusion method with carbapenems according to the Clinical and Laboratory Standards Institute-CLSI (2010), and the research of the resistance to carbapenems gene bla KCP , by the strains Salmonella spp.…”
Section: Evaluation Of Biofilm Production Capacity and Detection Of Ementioning
confidence: 99%
“…Os genes utilizados na presente pesquisa (Tabela 2) foram selecionados com base em estudo realizado por Borges et al (2013) Borges et al (2013) e NCBI (2014) Para a extração do DNA transferiu-se 1mL da cultura ativa para um tubo tipo Eppendorf. O tubo foi submetido à centrifugação por 4min a 9000rpm, o sobrenadante foi descartado e o pallet ressuspendido em 100µL de água deionizada estéril.…”
Section: Identificação Dos Genes Relacionados Aos Fatores De Virulênciaunclassified
See 1 more Smart Citation